Proximate analysis of sweet potato toasted granules (2010)
Sweet potato is an important root crop in the food system of many african countries. The yield, nutrition and economic potential of sweet potato have been identified as very high. In this study, sweet potato was processed and toasted into granules. The proximate analysis performed on the toasted granules showed protein, fat, ash, fiber, starch, moisture and low sugar content after processing. It was discovered that the more fermented the paste before toasting the lower the sugar content and more acceptable the taste. Therefore, the remarkeable low sugar content indicates potential usefulness as a dietary supplement of diabetics patients. Its fiber content will had bulk and aid digestion, thus preventing constipation. Therefore, awareness should be created on the innovation for the management of the diabetics.